The Growth of Prokaryotes in Antarctic Sea Ice: Implications for Ancient Ice Communities - David Nichols (2005)
The development of permanently cold environments on Earth is a relatively recent event in terms of aerobic prokaryotic evolution. Diversification of early amphiaerobes is believed to have occurred 1.8 to 2.4 billion years ago (56), while the formation of Earth’s first permanently cold environment, the cold deep ocean (less than 10 °C), is thought to have occurred only 38 million years ago (30). Presently over 80% of the Earth’s biosphere is permanently cold, that is, less than 5 °C (53). While the evolution of bacteria capable of surviving and requiring permanently cold temperatures for growth may be relatively recent, these.